Commonly used stimulants: Sleep problems, dependence and psychological distress. (1st August 2015) - Ogeil, Rowan P.; Phillips, James G.
Highlights: An online survey was completed by 166 participants with a mean age of 28 years. Sleep quality was poorer in those dependent upon caffeine or nicotine. Despite males reporting higher levels of drug use, females reported poorer sleep. Strong links between poor sleep quality and psychological distress were found. Abstract: Background: Caffeine and nicotine are commonly used stimulants that enhance alertness and mood. Discontinuation of both stimulants is associated with withdrawal symptoms including sleep and mood disturbances, which may differ in males and females. The present study examines changes in sleep quality, daytime sleepiness and psychological distress associated with use and dependence on caffeine and nicotine. Methods: An online survey comprising validated tools to assess sleep quality, excessive daytime sleepiness and psychological distress was completed by 166 participants (74 males, 96 females) with a mean age of 28 years. Participants completed the study in their own time, and were not offered any inducements to participate. Results: Sleep quality was poorer in those dependent upon caffeine or nicotine, and there were also significant interaction effects with gender whereby females reported poorer sleep despite males reporting higher use of both stimulants. Caffeine dependence was associated with poorer sleep quality, increased daytime dysfunction, and increased levels of night time disturbance, while nicotine dependence was associated with poorer sleep quality and increased use of sleep medication and sleep disturbances. There were strong links between poor sleep and diminished affect, with psychological distress found to co-occur in the context of disturbed sleep. Conclusions: Stimulants are widely used to promote vigilance and mood; however, dependence on commonly used drugs including caffeine and nicotine is associated with decrements in sleep quality and increased psychological distress, which may be compounded in female dependent users.